(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Bangladesh has made tremendous strides in the development of modern rice varieties as well as boosting domestic rice production up. Therefore, this study aims to investigate the performance, identify the criteria and constraints, as well as find out the drivers influencing the adoption and intensity of adoption of BRRI developed modern rice cultivars in Boro season. A total of 780 randomly selected farmers were interviewed using a structured schedule from 13 upazilas of the Mymensingh district. Descriptive statistics used mainly to evaluate the socio-economic characteristics of farmers as well as the performance of BRRI varieties, and a censored Tobit regression model employed to figure out the drivers of BRRI variety adoption. The results showed that in the Boro season about 85% area of Mymensingh district was covered by BRRI varieties and yielded 5.93 t/ha on average. The outcome of the model indicates that variables such as farmers schooling, farm size, farming experience, training and extension service, demonstration, distance to the nearby market, higher yield capacity, number of cultivated varieties, higher price, and good taste were influential drivers of adopting BRRI variety during the Boro season. This finding recommends that breeders should emphasize the farmers’ preferences while developing varieties, as well as providing training and field demonstration for spreading newly established BRRI rice varieties. J Bangladesh Agril Univ 18(3): 660–666, 2020 https://doi.org/10.5455/JBAU.102132